Unplanned Purchase and Personal Debt: A Relation Analysis - Bonomo, Brunno (2017)
Literatures on impulse purchasing and indebtedness have been studied separately for decades, mainly in studies in the areas of marketing and finances. Thereby, this research proposes a multidisciplinary study amidst the phenomenon that is impulse purchasing and personal debt. Therefore, the central objective of this study was to identify if there is a relation between impulse purchasing and personal debt within traditional retail. To reach this objective, a quantitative research was conducted, descriptive, cross-sectional and survey type. The sample contemplated 435 customers in a store. The data were collected in the environment of a shoe retail store in the country side of Espírito Santo - Brazil. The relations between variables were analyzed by the means of a multiple regression.  The results showed evidence that, to the respondents, impulse purchasing can affect their income, but personal indebtedness is not necessarily prevenient from unplanned purchase.